“It is Important to Prepare Ourselves for the Future Career”: A Study of Indonesian Student’s Self-Directed Experience on Career Exploration - Ragwan Mohsen Alaydrus; Siti Rafiah Abd. Hamid (Universitas Mathla'ul Anwar Banten, 2019)
Lack of career exploration leads to career indecisiveness among Indonesian high school students. According to some studies, successful career exploration is determined by students’ initiative. However, no consistent answer about factors that make the students self-directedly engage in career exploration. This study is aimed to explore student’s self-directedness during the career exploration, including the factors that encourage student’s career exploratory behavior. This single case study used semi-structured interview and document analysis to investigate the experience of one Indonesian high school student. Two themes emerged from the data: involvement factor in career exploration, which determined by internal and external influence, and qualities of self-directedness, which is reflected by the employment of strategies and self-awareness. Recommendation for parents and educators to provide exposure to various activities, explicit teaching of self-directed learning and related skills is also essential to build students’ initiative in career exploration.